Case report: Resolution of Guillain-Barré syndrome in a patient with dual primary tumors after treatment with rituximab - Zhang, Desheng; Wang, You; Zhou, Fuxiang (Frontiers in Neurology, 2024)
Guillain-Barré syndrome (GBS) is a rare immune-related adverse event (irAE) that can occur in solid tumors such as hepatocellular carcinoma, gastric cancer, breast cancer, and colorectal cancer. It is characterized by progressive myasthenia and mild sensory abnormalities. The emergence of immune checkpoint inhibitors (ICIs) has significantly improved cancer patients’ life expectancy but can also trigger various irAEs, including GBS. We report a rare case of GBS in a 64-year-old male patient with dual primary tumors of the colon and stomach who received toripalimab and chemotherapy for liver metastases. After five treatments, the patient experienced weakness and numbness in his limbs. Lumbar puncture, electromyography, and other tests confirmed the diagnosis of GBS. Intravenous immunoglobulin (IVIG) and methylprednisolone did not improve the patient’s symptoms, but rituximab, which is not a standard regimen for GBS, was effective in eliminating B cells and improving symptoms. Following this, we effectively shifted from a regimen combining immunotherapy and chemotherapy to a targeted therapy regimen, resulting in prolonged patient survival. Currently, limited studies have been undertaken to evaluate the efficacy of rituximab in managing refractory neurological adverse events associated with ICI therapy. Using this case, we reviewed similar cases and formed our views.